Regional and Local Scale Lineament Analysis Using ALOS PALSAR DEM for Geological Structure Identification in the Sentul Area, West Java, Indonesia - Aqeel Kayana Wiendra (Syntax Corporation Indonesia, 2026)
Geological structures play an important role in controlling geomorphological development and tectonic deformation within the Sentul area, West Java, Indonesia. However, detailed structural mapping is often constrained by limited field accessibility and spatial coverage. This study, Regional and Local Scale Lineament Analysis Using ALOS PALSAR DEM for Geological Structure Identification in the Sentul Area, West Java, Indonesia, aims to identify geological structures using ALOS PALSAR Digital Elevation Model (DEM) data integrated with multi-directional hillshade analysis, lineament extraction, rose diagram analysis, and lineament density mapping within a Geographic Information System (GIS) environment. The multi-directional hillshade effectively enhances topographic discontinuities, including aligned valleys, ridge alignments, and slope breaks, enabling the extraction of structural lineaments at both regional and local scales. A total of 347 regional lineaments and 53 local lineaments were identified, indicating a well-developed structural network throughout the study area. Rose diagram analysis reveals a dominant structural orientation trending NNE–SSW to NE–SW, suggesting consistent structural control across multiple spatial scales. Lineament density mapping indicates that the highest concentration of structural features is located within the Hambalang–Tangkil sector, while local-scale analysis highlights several NE–SW-oriented structural corridors within the Sentul area. The consistency observed among DEM-derived, hillshade, lineament, density, and orientation analyses suggests that the identified lineaments represent potential structural discontinuities associated with the regional tectonic framework of the Bogor Zone. These findings demonstrate that ALOS PALSAR DEM, combined with GIS-based terrain analysis, provides an effective and cost-efficient approach for geological structure identification and can support future geological investigations, geohazard assessment, and regional land-use planning in West Java.